"O Amherst, Where is Thy Shame?": Republican Opposition to Federalist Policies in a New England Town. Issue 3 (9th August 2018) - Siggelakis, Susan J; Mignanelli, Nicholas
Abstract: This paper examines the impact of Federalist Party policies in the small New Hampshire town of Amherst during the last two years of the eighteenth century. Drawing upon local histories and primary sources, including private letters and local newspaper archives, the authors portray a town rent by internal divisions of party, religion, and lifestyle. Their conflicts are set within the larger context of American national politics and the diverse voices throughout the states, concerned about the direction of the new republic. Key local actors in the struggle to petition the United States Congress over the Alien, Sedition, and Direct Tax Acts are described, along with their various interactions. Satiric poetry is shown as one important way in which partisans attacked one another through the press, in addition to threats and rumor-mongering. Yet, cogent arguments about political power are also present in these interactions, attesting to an engaged citizenry that is invested in this new representative democracy during the perilous last years of the century. This paper concludes with a description of how the tension among two different groups of partisans, Federalist and Republicans, led to the official splintering of one town into two, with the more strongly Republican section emerging as the new town of Mont Vernon.